Challenges in conducting population-based seroepidemiology survey of COVID-19 in Lagos State, Nigeria - Adewale Kayode Ojogbede; Tajudeen Akanji Bamidele; Oluwagbemiga Aina; Toyosi Raheem; Azuka Okwuraiwe; Olufemi Amoo; Kazeem Adewale Osuolale; David Oladele; Abideen Salako; Fehintola Ige; Adesola Zaidat Musa; Ifeoma Idigbe; et al. (BMC, 2023)
Abstract Population-based study is known to be a very essential type of study during and after a pandemic or epidemic, as it provides crucial information on the incidence, prevalence, and risk factors of the disease in question. There has been limited information about the challenges faced in conducting such surveys in Nigeria. In this paper, we will share our experience, and describe the challenges faced in conducting a population-based seroepidemiological study of COVID-19 in Lagos, Nigeria. Some challenges were peculiar to specific Local Government Areas (LGAs) while others were general. The challenges include general misconceptions of community members about health research, difficulties in mapping houses, planning for data collection, standardizing data collection, working in hard-to-reach communities when resources were limited as well as difficulty in collection of blood and naso-oropharyngeal swabs. Ways of overcoming these problems, lessons learnt, and recommendations are hereby discussed.